2012
DOI: 10.1128/jvi.06310-11
|View full text |Cite
|
Sign up to set email alerts
|

The US16 Gene of Human Cytomegalovirus Is Required for Efficient Viral Infection of Endothelial and Epithelial Cells

Abstract: bThe human cytomegalovirus (HCMV) US12 gene family comprises a set of 10 contiguous genes (US12 to US21), each encoding a predicted seven-transmembrane protein and whose specific functions have yet to be ascertained. While inactivation of individual US12 family members in laboratory strains of HCMV has not been found to affect viral replication in fibroblasts, inactivation of US16 was reported to increase replication in microvascular endothelial cells. Here, we investigate the properties of US16 further by asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 50 publications
2
60
1
Order By: Relevance
“…HCMV TR was derived from an ocular specimen (47), and after a few passages on fibroblasts, it was cloned into a bacterial artificial chromosome (48,49). Reconstitution of infectious TR was performed as previously described (50) by cotransfecting HFFs with the corresponding TR bacterial artificial chromosome and a plasmid expressing HCMV pp71. Reconstituted infectious virus retained the ability to infect endothelial and epithelial cells, as well as monocytes and macrophages (49,50).…”
Section: Hcmv Preparations and Infection Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCMV TR was derived from an ocular specimen (47), and after a few passages on fibroblasts, it was cloned into a bacterial artificial chromosome (48,49). Reconstitution of infectious TR was performed as previously described (50) by cotransfecting HFFs with the corresponding TR bacterial artificial chromosome and a plasmid expressing HCMV pp71. Reconstituted infectious virus retained the ability to infect endothelial and epithelial cells, as well as monocytes and macrophages (49,50).…”
Section: Hcmv Preparations and Infection Conditionsmentioning
confidence: 99%
“…Reconstitution of infectious TR was performed as previously described (50) by cotransfecting HFFs with the corresponding TR bacterial artificial chromosome and a plasmid expressing HCMV pp71. Reconstituted infectious virus retained the ability to infect endothelial and epithelial cells, as well as monocytes and macrophages (49,50). HCMV VR1814 is a derivative of a clinical isolate recovered from a cervical swab of a pregnant woman (51).…”
Section: Hcmv Preparations and Infection Conditionsmentioning
confidence: 99%
“…Most known restrictions to HCMV tropism in ECs occur early in the infection process, residing at the level of viral entry (62) or delivery of the viral genome to the nucleus (58). As such, one plausible explanation for the observed defect in replication may be that a protein encoded in the UL133-UL138 locus is required for viral entry into ECs, similar to the UL128-UL131A locus.…”
Section: Ul133-ul138mentioning
confidence: 99%
“…Studies in MCMV revealed a requirement for the M45 gene to inhibit apoptosis for productive replication specifically in ECs and macrophages (57). Recently, the US16 HCMV gene was reported to be required for delivery of viral genomes and tegument proteins to the nuclei of ECs but not fibroblasts (58). Viruses containing disruptions in US16 are defective at the immediate-early (IE) stage and all subsequent stages of infection in ECs.…”
mentioning
confidence: 99%
“…Nonetheless, very little is known about the expression patterns and functions of individual US12 proteins in infected cells. In this regard, the intracellular localization of the US14, US16, US17, and US18 proteins was determined by immunofluorescence analyses that revealed an association with the cytoplasmic virion assembly compartment (cVAC), thus suggesting that their functions may be linked to virion maturation and egress (13,14). In support of this hypothesis, it was observed that inactivation of the US17 gene in producer fibroblasts results in increased production of noninfectious viral particles that can, in turn, deliver augmented amounts of the pp65 immunomodulatory tegument protein to newly infected cells, thus altering the regulation of both intrinsic and innate responses of cells infected with the US17-deficient virus (15).…”
mentioning
confidence: 99%